Meanings and Manifestations of the Anarchist-Utopian Ethos in Adult Education - Roger Boshier (Adult Education Research Conference, 2004)
Anarchist-utopians in adult education ascribe considerable significance to learning that occurs away from the surveillance of formal education. First generation anarchist-utopianism was different to that now shaping educational practice. In adult education, leading anarchist-utopians included Ivan Illich and John Ohliger.